HarvestStat: A global effort towards open and standardized sub-national agricultural data - Davis, Kyle Frankel; Anderson, Weston; Ehrmann, Steffen; Flach, Rafaela; Meyer, Carsten; Proctor, Jonathan; Ray, Deepak; You, Liangzhi; Foley, Michael; Kerdiles, Hervé; Hultgren, Andrew; Huybers, Peter; et al. (IOP Publishing, 2025)
Agricultural production statistics underpin diverse research efforts and development activities. Yet despite their critical importance, efforts to collate, update, and harmonize detailed sub-national agricultural production statistics are frequently redundant and incomplete due to the substantial time, effort, and resources required. The persisting lack of coordination and standards in the food systems data community wastes valuable resources and hinders advances in action-oriented food systems knowledge. Here we introduce the HarvestStat sub-national data consortium as an open-source, collaborative, and transparent model to overcome these challenges. HarvestStat is collaboratively producing publicly available databases and datasets for the food systems community and the broader environmental and sustainability sciences by moving beyond closed and disjointed data-gathering efforts. We are guided by core principles of complete data openness—prioritizing high standards of quality assurance; active inclusion—emphasizing involvement from local experts; and collaboration—fostering engagement across communities of data producers and users. We extend an open global call to action, inviting organizations and individuals to engage in advancing this critical agenda.